Effectiveness of Cyanoacrylate in Reducing Seroma Formation in Breast Cancer Patients Post-Axillary Dissection: A Randomized Controlled Trial - Al-Masri, Mahmoud; Alawneh, Fade; Daoud, Faiez; Ebous, Ali; Hamdan, Basem; Al-Najjar, Hani; Al-Masri, Rama; Abufara, Marwan (Frontiers in Oncology, 2021)
Background/Purpose Seroma is a common complication after axillary dissection in women with node-positive breast cancer. We aim to determine the effect of Cyanoacrylate on reducing seroma formation in patients undergoing axillary dissection. This a randomized clinical trial. Methods This is a single-center, randomized, single-blinded, and two-arm parallel study. Women with node-positive breast cancer eligible for axillary dissection were enrolled. Patients with a Body Mass Index (BMI) greater than 35 kg/m2, those who underwent immediate breast reconstruction, and/or received neoadjuvant chemotherapy were excluded. Patients were randomized in a 1:1 ratio, and were stratified according to their age, BMI, tumor size, and operation type. The primary endpoint was the total seroma volume (the total drained volume and the total aspirated volume after drain removal). Data presented as mean and range when applicable. Results 111 patients were randomized (Cyanoacrylate 57; control 54). 105 patients were analyzed. Sixty-nine patients underwent breast conserving surgery, and 36 underwent modified radical mastectomy. There was no difference in the total seroma volume between the Cyanoacrylate vs. control arms (1,304 (60–4,950) vs. 1,446 (100–5,223) ml, p=0.458). Wound infection, flap necrosis, number of manual aspirates, and hematoma formation were not statistically different between the two groups. Time to drain removal was shorter in the Cyanoacrylate arm (11.04(3–23) vs. 13.84(3–37) days, p=0.015). The use of Cyanoacrylate was not cost effective (586.93 (550–748) vs. 29.63 (0–198), p<0.001). Higher seroma volume was correlated with modified radical mastectomy, older age, and BMI more than 30 kg/m2. Conclusion Cyanoacrylate did not reduce seroma formation and its use was not cost effective. Clinical Trial Registration clinicaltrials.gov, identifier NCT02141373.